1994
DOI: 10.1046/j.1365-2648.1994.20010183.x
|View full text |Cite
|
Sign up to set email alerts
|

Humour in nursing care

Abstract: Humour is an integral part of everyday life and therefore also a component of the care and treatment of patients in the modern health care system. This paper looks at the role of humour in practical nursing in the light of earlier research literature on the subject. It also describes some preliminary results of our studies on the meaning of humour to professional nurses. We opted to use a qualitative approach in this study because the focus of interest was on an issue that has received only little attention in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 10 publications
3
48
0
3
Order By: Relevance
“…These results corroborate studies (Lindau et al, 2007;Steinke, 1997) Thirdly, for 'attitudes/behaviours due to the demonstration of sexual expression', the most prevalent category was 'using humour' (50.0%). These results corroborate a qualitative study by Astedt-Kurki and Liukkonen (1994), in which most of the FCs thought that humour played a major role in improving their work environment.…”
Section: Discussionsupporting
confidence: 88%
“…These results corroborate studies (Lindau et al, 2007;Steinke, 1997) Thirdly, for 'attitudes/behaviours due to the demonstration of sexual expression', the most prevalent category was 'using humour' (50.0%). These results corroborate a qualitative study by Astedt-Kurki and Liukkonen (1994), in which most of the FCs thought that humour played a major role in improving their work environment.…”
Section: Discussionsupporting
confidence: 88%
“…Patently, there will be times when humor is not appropriate [30]. However, according to most studies [3133] humor in care is something valuable which fosters a relationship, eases tension and more. Using physical contact and humor when caring for a patient requires great mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…du Pre 1998; Martin 2001; Thorson et al 1997) work on humor and organization has pursued another functional line, the physiological and general health and well-being benefits of humor (Caudron 1992;Kerrkanen et al 2004;Kupier et al 1992;Morreall 1997). This work is related to some very practical applications of humor in medical settings with the use, for example, of "clown doctors" (Buchanan 2000) and humor to reduce anxiety among patients (Astedt-Kurki and Liukkonen 1994). In a related manner, other studies have shown a relationship between humor and stress reduction and other types of coping behavior (Cann et al 1999;Lefcourt et al 1997;Lefcourt and Thomas, 1998;Martin 2006;Martin et al 1993;Nezlek and Derks 2001;White and Winzelberg 1992); work extended into organizational domains (Avtgis and Taber 2006;Fry 1995;Lefcourt et al 1995;Moran 1990;Moran and Massam 1997;Rosenberg 1991).…”
Section: The Funny Function: Orthodox Functionalist Research On Humomentioning
confidence: 99%